Direitos humanos na empresa e sua efetivação através do compliance - Silva, Deise Cássia de Macêdo (2022)
The notorious growth of companies, with an increase in their economic and social power, has increased the concern with the preservation of human rights in the corporate sphere, raising initiatives aimed at ensuring respect for human dignity both within corporations and in societies for them impacted. In turn, the performance in compliance has been developed in the scenario of constitutionalization of law based on the notion that acting in accordance with internal and external regulations can provide entrepreneurs with savings in resources and a better image of the corporation in the market. From this perspective, this research will focus on the development of the following problem: is it possible to enforce human rights in the company through compliance? As specific objectives will be addressed: to analyze the relationship between human rights and companies, presenting the main national and international initiatives in this area; examine the theoretical aspects of the company, its constitutionalization and principle; investigate the corporate compliance institute, outlining its main forms of application, and raise its applicability in the enforcement of human rights in the business environment. The approach method used in the research will be the hypothetical-deductive one, from the evaluation of the proposed hypothesis to find an answer to the problem through a deduction process. The procedure adopted will be, especially, exploratory bibliographic research, using qualitative research techniques, based on theoretical data. The study seeks, from the theoretical references discussed, to contribute to debates about the implementation of human rights in the corporate world, suggesting, in the end, the use of compliance, in its various forms.